SAMKHYA DI BALI: TELAAH PERUBAHAN PARADIGMA MELALUI PENGGUNAAN BAHASA DALAM AJI SANGKYA - Sindhu Gitananda, W.A (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The canonical relation between the samkhya philosophy (based on the Samkhya Karika) and Aji Sangkya can be obviously observed through the title. The dualistic –discrimination of the purusha and the prakriti—discourse is always embedded to the samkhya system of philosophy since it was coined by Kapila (600 BC). This discourse has been spread out to all over the world, including the Archipelago. The influence can be read in several texts as Wrhaspati Tattwa and Tattwa Jnana (14th—15th AD) but the discourse of dualistic has been very different, supposedly undergoing a par- adigm shift. The focus of this article is to analyze the paradigm shift signified by the language use based on the radical hermeneutics (deconstruction) supported by the contextual stylistics approach. The result shows that the paradigm shift of the samkhya philosophical discourse is found in Aji Sangkya in several levels as ontological shift of philosophical discourse from materialistic-spirit- ualistic into saivistic-humanistik, from anxiety into saivistic, shift in the philosophical discourse of prakriti atau pradhana, purusha, buddhi atau mahat, ahamkara (ahangkara), manas, and all of the levels of paradigm shift are accumulated in the shift of the philosophical discourse structure or pattern of manifestation. This means that the Aji Sangkya of the Balinese modern philosophical text can be taken as the reformation of the philosophical discourse of samkhya.